A review on nutritional quality of animal and plant-based milk alternatives: a focus on protein - Karoui, Romdhane; Bouaicha, Inès (Frontiers in Nutrition, 2024)
In recent years, the demand of consumers for products rich in protein is of significant growth. Due to its structure in tissues, protein is considered an essential nutrient for maintenance and growth. It is well known that dairy foods differ from plant-based milk alternatives in their composition. In addition to protein content, nutrients in milk and plant-based beverages vary greatly in composition and content, such as: Calcium, fiber and fat. The nutritional quality of dairy protein sources depends on both their amino acid composition and bioavailability. Indeed, dairy products are considered to be excellent sources of proteins with high Digestible Indispensable Amino Acid Score (DIAAS) values varying from 100 to 120. However, plant proteins are considered to have generally lower essential amino acid contents and lower DIAAS values than dairy proteins. For example, pea and rice proteins are known to have medium and lower DIAAS with values of 62 and 47, respectively. The present review is dedicated to study the nutritional quality of animal and plant-based milk alternatives, where a focus on protein composition and amount are determined.